GP73, a novel Golgi-localized protein upregulated by viral infection - Kladney, Raleigh D. (Gene, 2000)
We report the isolation and characterization of GP73, a novel 73 kDa human Golgi protein. The GP73 cDNA was cloned by differential screening of a cDNA library derived from the liver of a patient with adult giant-cell hepatitis (GCH), a rare form of hepatitis with presumed viral etiology. In vitro transcription–translation studies indicate that GP73 is an integral membrane protein, and immunolocalization experiments using epitope-tagged GP73 demonstrate that the protein is localized to the Golgi apparatus. Northern blot analysis of RNA from multiple human tissues reveals a single GP73 mRNA transcript with a size of approximately 3.0 kb. Immunohistochemical studies using rabbit polyclonal antisera directed against recombinant GP73 demonstrate that the protein is preferentially expressed by epithelial cells in many human tissues. In normal livers, GP73 is consistently present in biliary epithelial cells, whereas hepatocytes show little or no signal. In contrast, livers of patients with GCH display strong GP73 immunoreactivity in multinucleated hepatocytes. GP73 mRNA and protein are expressed in highly differentiated HepG2 hepatoma cells after infection with adenovirus in vitro. We conclude that GP73 represents a novel, epithelial cell-specific integral membrane Golgi protein that can be upregulated in response to viral infection.